AI in the Classroom: A rapid evaluation of AI-generated lesson plans in Islamabad’s public schools - Aslam, Nawaz; Qureshi, Ghada; Hassan, Syed Mustafa (EdTech Hub, 2025)
This report presents a rapid evaluation of AI-generated lesson plans currently being used in public schools in rural and urban Islamabad under the National Institute of Excellence in Teacher Education (NIETE). These centrally developed, scripted lesson plans are aligned with the national curriculum and built on the Gradual Release of Responsibility (GRR) model, with additional elements of the 5E and Inquiry-Based Learning (IBL) models in science, and the Concrete-Pictorial-Abstract (CPA) model in maths. Using a mixed-methods approach—including teacher surveys, focus group discussions, key informant interviews, and an expert rubric-based review—the study assesses the lesson plans' quality, relevance, and adaptability. Teachers expressed strong support for the lesson plans, especially in terms of reduced workload and structured delivery, though concerns were raised around flexibility, contextual responsiveness, and teacher agency. While the study does not evaluate student learning outcomes, it provides actionable insights and recommendations for improving the design, support, and implementation of AI-generated instructional tools, particularly as the programme scales to other provinces in Pakistan, such as Balochistan. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15077892 ZenodoArchiveConcept: 15077891 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1104 10.53832/edtechhub.1105 10.53832/edtechhub.1107 10.53832/edtechhub.1108 2405685:FR4GREKJ 2405685:XG7G3FDM
Keywords: _r:AddedByMyEducationEvidence

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13767575 ZenodoArchiveConcept: 13767574 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1050 10.53832/edtechhub.1060 2405685:K28H9QDG 2405685:ZAKFGN9M
Keywords: _r:AddedByMyEducationEvidence

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7074857 ZenodoArchiveConcept: 7074856 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6326179 10.5281/zenodo.7074857 10.53832/edtechhub.0114 2405685:K5BJUBRE 2405685:REW8F5TJ 2405685:U6G7C62D
Keywords: _r:AddedByZotZen

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

Teacher Continuous Professional Development in Tanzania: Lessons Learnt - Chachage, Kristeen; Thakrar, Jay (EdTech Hub, 2023)
This report shares the experience and learning from the activities carried out as part of the Government of Tanzania's efforts to operationalise its National Framework for Teacher Continuous Professional Development (TCPD), which shifts TCPD from discreet workshops to cost-effective, ongoing, school-based professional development. It is among the first of its kind at a national level, particularly in low- and middle-income country contexts. Through a collaborative and responsive approach of adaptive technical assistance and innovation, the EdTech Hub team supported Government of Tanzania partners in developing and implementing a technology-enhanced, school-based, national TCPD system. This report begins with an overview of the activities implemented and then consolidates reflection through nine lessons learnt that could help inform current and future thinking on the design, delivery, and funding of TCPD programming in Tanzania. The TCPD reflected in this report is specific to Tanzania's teaching and learning environment. While we recognise that environments can vary widely, even between countries with similar goals and objectives, the report also seeks to contribute to any current and future analyses that collate features of effective TCPD from around the world. Keywords: teacher professional development; teacher training; technology; learning management system; communities of learning; teacher needs assessment; An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7677950 ZenodoArchiveConcept: 7677949 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7677950 10.53832/edtechhub.0157 2339240:RBNTBT7Z 2405685:9WBV8KPN 2405685:EGL4QHDZ
Keywords: _r:AddedByZotZen

Learning with technology during emergencies: A systematic review of K-12 education - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel W. G. (British Journal of Educational Technology, 2021)
Emergency situations that cause damage to educational buildings or require the closure of schools due to unsafe health, environmental, or political conditions can be an unwelcomed interruption to education. Indeed, the recent COVID-19 pandemic created the largest disruption of education in history, affecting 94% of the world's student population. In emergencies, technology is often utilised as part of a crisis response protocol by continuing education using emergency remote education (ERE). The purpose of this study is to determine how technology has been used to continue K-12 learning remotely during an emergency. This systematic review included an aggregated and configurative synthesis to examine extant empirical work over eleven years, from January 2010 to December 2020. Following a rigorous, PRISMA selection process, 60 articles were included in the final analysis from 48 countries. Grounded coding of the strategies used for learning revealed the following categories: communication, delivery systems, student ERE readiness, partnerships, promoting student learning and engagement, and resources. Grounded coding of the technologies revealed that types of technologies used were divided into two major categories: Internet-based and non-Internet based, with the majority using Internet-based technologies. Practitioner notes What is already known about this topic The COVID-19 pandemic has caused school closures across the globe and prevented in-person school teaching. The rapid shift to distance education in schools can be conceptualised as ‘emergency remote education’ (ERE). Prior ERE research focused on bounded geographic locations where localised emergencies occurred. What this paper adds This provides the scholarly community with a unique systematic review of existing academic research on K-12 ERE implementation in emergencies. This provides aggregated data and analysis on the past 11 years of the types of emergencies, participants, subject domain, technologies used, and location information. This provides findings of the types of remote teaching strategies involving technology used to continue K-12 learning in emergency situations. This provides a set of recommendations on ERE for teachers, school leaders, policy makers, and funders. This provides researchers with a review of the field with identification of gaps and future research opportunities. Implications for practice and/or policy Recommendations regarding ERE are provided in this paper that will be of benefit to K-12 teachers, school leaders policymakers, and funders in the continuing COVID-19 pandemic and future emergencies. The research gaps highlighted in this paper, such as the lack of studies conducted in low and low middle-income countries, are presented with suggestions for much needed future research. This can lead to changes in practice and policy.
ZenodoArchiveID: 5652042 _eprint: https://bera-journals.onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.13114 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13114 10.5281/zenodo.5652042 2339240:ELI3E5RF 2339240:TJNJX997 2405685:3KJJW6XZ 2405685:9V69ZAFP 2405685:BDG6N6PJ 2405685:JE8I8566 2405685:YY7LXWQB
Keywords: COVID-19; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _yl:b; _zenodo:submitted; disasters; emergencies; emergency remote education; pandemic

EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14622107 ZenodoArchiveConcept: 14622106 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1085 2405685:KIEIX7NP
Keywords: _r:AddedByMyEducationEvidence

MEWAKA National Teacher Development Reform in Tanzania: Design-Based Implementation Research: Cycle 1 Findings - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, G.; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fred; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teacher Continuous Professional Development [TCPD]) is a landmark, school-based teacher professional development programme being implemented nationally by the Government of Tanzania, with the ultimate aim of raising learning outcomes in schools. EdTech Hub, Aga Khan University, and the Tanzania Institute of Education (TIE) are conducting research to iteratively enhance the MEWAKA implementation at primary school level and to understand the role that technology can play in scaling TCPD. This report presents the findings and recommendations from the first cycle of design-based implementation research (DBIR) conducted in rural schools in the Lindi region. Following a pilot peer facilitator workshop, data was collected through observation and self-reporting methods between September and December 2022. The aims were to capture stakeholders' perspectives at all levels of the education system and to see how schools are implementing the programme on the ground. The emerging findings and recommendations are being used to inform the redesign and further implementation of this TCPD model, and were used to identify key areas to test and investigate in the second cycle of the DBIR in 2023. Keywords: teacher professional development; design-based implementation research; Tanzania; primary education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7783382 ZenodoArchiveConcept: 7783381 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7783382 10.53832/edtechhub.0167 2339240:R9JRWMKC 2405685:6CC8GQZP 2405685:XHJC3W67
Keywords: _r:AddedByZotZen